2005
DOI: 10.1172/jci24487
|View full text |Cite
|
Sign up to set email alerts
|

Oral tolerance in the absence of naturally occurring Tregs

Abstract: Mucosal tolerance prevents pathological reactions against environmental and food antigens, and its failure results in exacerbated inflammation typical of allergies and asthma. One of the proposed mechanisms of oral tolerance is the induction of Tregs. Using a mouse model of hyper-IgE and asthma, we found that oral tolerance could be effectively induced in the absence of naturally occurring thymus-derived Tregs. Oral antigen administration prior to i.p. immunization prevented effector/memory Th2 cell developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
421
1
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(452 citation statements)
references
References 69 publications
18
421
1
8
Order By: Relevance
“…5B). To confirm the above results, we repeated the CNS2 demethylation study using the oral tolerance model (5,54). FACS-sorted naive OT-II T cells were transferred into congenically marked WT B6 mice followed by the administration of OVA to induce pTregs.…”
Section: Vitamin C Is Essential For Cns2 Demethylation In Ptregsmentioning
confidence: 80%
See 2 more Smart Citations
“…5B). To confirm the above results, we repeated the CNS2 demethylation study using the oral tolerance model (5,54). FACS-sorted naive OT-II T cells were transferred into congenically marked WT B6 mice followed by the administration of OVA to induce pTregs.…”
Section: Vitamin C Is Essential For Cns2 Demethylation In Ptregsmentioning
confidence: 80%
“…1E) and pTregs (Figs. [5][6], suggesting that the uptake of vitamin C through SVCTs is critical in the Tet-mediated CNS2 demethylations. Exceptionally, thymically derived Tregs were resistant to sulfinpyrazone treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory T cells can be divided into subsets on the basis of their development (natural or acquired), cell surface phenotype, secreted proteins and function. Acquired Tregs express FOXP3 [3,4] and, like natural Tregs, are dependent on cell contact (acquired Tregs). They are anergic and secrete very little or no IL-2 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that specialized populations of CD4 + /CD25 + regulatory T cells (Treg) control intestinal inflammation induced by immune response, via IL-10-and TGFb1-dependent mechanisms. In addition, naïve peripheral T cells may acquire a Treg phenotype under the influence of TGFb1 [8,33,74].…”
Section: How Tgfb1 Signal Influences Colon Mucosa Functionmentioning
confidence: 99%